(untitled) (Innovative professional education, 2024)
The importance of sustainable development as one of the key concepts of modern society aimed at achieving a balance between economic, environmental and social aspects is described. It is determined that Ukraine is an active participant in international initiatives, such as Agenda 2030, integrating them into national policy. The need to develop professional education to ensure the training of specialists capable of meeting the current challenges of sustainable development is substantiated. It is revealed that the sustainable development of vocational education is based on a combination of theoretical knowledge and practical skills and is realized through cooperation between the state and business. The impact of public-private partnerships on reforming the vocational education system, in particular through the creation of new educational and training programs and infrastructure modernization, is considered. The participation of the private sector in financing vocational education is outlined, taking into account the current needs of the labor market. The author emphasizes the importance of integrating innovative technologies into the educational process, which contributes to the formation of the necessary competencies of future professionals, and adapting educational programs to new challenges facing the national economy and labor market.